Answer:
9.8 lbs
Step-by-step explanation:
4 1/3 + 5 5/6= 10 1/6
20 - 10 1/6 = 9.8
Answer:
(7 x - 1) (x + 1)
Step-by-step explanation:
Factor the following:
7 x^2 + 6 x - 1
Factor the quadratic 7 x^2 + 6 x - 1. The coefficient of x^2 is 7 and the constant term is -1. The product of 7 and -1 is -7. The factors of -7 which sum to 6 are -1 and 7. So 7 x^2 + 6 x - 1 = 7 x^2 + 7 x - x - 1 = (7 x - 1) + x (7 x - 1):
(7 x - 1) + x (7 x - 1)
Factor 7 x - 1 from (7 x - 1) + x (7 x - 1):
Answer: (7 x - 1) (x + 1)
I'm terrible at math, so I'm sorry if I'm totally wrong, but I'm assuming you just take the average:
20+28=48m
48/2=24m
On average, it may take them 24m if they work together.